Old Wine in the New Bottle: Dress Code in Malaysia Hotels - Tamsang Andi Kele, Andi; Che Shaari, Sharija; Ariffin, Roseni; Giman Stephen, Steward (International Journal of Engineering and Technology, 2018)
The female workforce in Malaysia has increased tremendously over the years. Ironically, despite Islam position perpetually enshrined in the constitution of the country as the official religion  and the ever increasing number of Muslim women in the workplace, the prohibition of hijab or  widely called ‘tudung’ is widely and openly practiced by the hotel industry. In the hospitality industry, employer requires employees to abide the industry grooming standard and this is usually done through a clearly defined dress code policy. However, dress code standards are usually challenged due different treatment based on religion or gender. Hence the research determine to acquire further understanding on the policy or practice of the dress code in Malaysia hospitality industry by determining the management’s acceptance towards religious requirement of employees’ dress code. A qualitative approach utilizing 15 in-depth interviews among the human resource managers in Malaysia was conducted to gain an understanding of underlying reasons and opinions regarding this issue. The research findings indicated that the hotel’s grooming standard, norm and leadership role as major elements that determine the management’s acceptance towards religious requirement of employees’ dress code. The outcome of this research can be used as a basis for the policymakers should any reformation for any relevant legislation to be carried out in future.